The attenuated ASFV strains MK-200 and FK-32/135 as possible models for investigation of protective immunity by ASFV infection. - Alexey D Sereda; Anna S Kazakova; Sanzhi G Namsrayn; Mikhail E Vlasov; Denis V Kolbasov (PLoS ONE, 2022)
African swine fever (ASF) is an infectious disease of domestic and wild pigs of all breeds and ages, with the acute form of the disease being characterized by high fever, hemorrhages in the reticuloendothelial system and a high mortality rate. Registered safe and efficacious ASF vaccines are not available. The development of experimental ASF vaccines, particularly live attenuated, have considerably intensified in the last years. There is much variability in experimental approaches undertaken by laboratories attempting to develop first generation vaccines, rendering it difficult to interpret and make comparisons across trials. ASF virus (ASFV) genotyping does not fully correlate with available cross-protection data and may be of limited value in predicting cross-protective vaccine efficacy. Recently, ASFV strains were assigned to a respective nine groups by seroimmunotype (from I to IX): in vivo the grouping is based on results of cross protection of pigs survived after their infection with a virulent strain (bioassay), while in vitro this grouping is based on hemadsorption inhibition assay (HADIA) data. Here we demonstrate the antigenic and protective properties of two attenuated ASFV strains MK200 and FK-32/135. Pronounced differences in the HADIA and in immunological test in animals allow us to consider them and the corresponding reference virulent strains of the ASFV of Mozambique-78 (seroimmunotype III, genotype V) and France-32 (seroimmunotype IV, genotype I) as useful models for studying the mechanisms of protective immunity and evaluation of the candidate vaccines.